Synthesis of porous polymers by polymerization‐induced phase separation in the addition reaction of multifunctional isocyanates and dithiol compounds. Issue 23 (12th August 2022) - Naga, Naofumi; Arai, Riku; Naruse, Yutaka; Ahmed, Kumkum; Nageh, Hassan; Nakano, Tamaki
Abstract: Porous polymers have been successfully obtained by an addition reaction of hexamethylene diisocyanate (HDI) trimer, isocyanurate type (IHDI), biuret type (BHDI), adduct type (AHDI), and dithiol compounds in toluene using triethyl amine (TEA) as a base catalyst. The feed ratio of TEA and the molecular structure of monomers affect the surface morphology and mechanical properties of the resulting porous polymers. In the case of the porous polymers obtained from the reactions with IHDI, aggregated or connected particles of about 1–1.7 μm in diameters were observed in scanning electron microscopy images. The porous polymers obtained from IHDI and dithiol compounds having long and/or flexible backbones showed low Young's modulus in the compression test. The Young's modulus of the AHDI‐1, 6‐hexanedithiol (HDT) porous polymer was lower than that of the corresponding IHDI‐HDT and BHDI‐HDT porous polymers, and two‐steps deformation derived from compression of the particles and filling of vacant space in the porous structure was observed. The addition reactions of polymeric diphenylmethane diisocyanate (PMDI) and alkane dithiol compounds also yielded the porous polymers, whose surface morphology was formed by connected small particles with diameters of about 0.5 μm. The porous polymers obtained from higher molecular weight PMDI showed higher Young's modulus. Abstract :